Reducibility of a nonlinear oscillation system with pulse influence in the neighborhood of an integral manifold - Dudnytskyi, P. M.; Petryshyn, R. I.; Samoilenko, A. M. (Ukrains’kyi Matematychnyi Zhurnal, 2004)
In the neighborhood of an asymptotically stable integral manifold of a multifrequency system with pulse influence at fixed times, we perform a decomposition of the equations for angular and position variables.